A Cultural Comparison of the ''Dark Constellations'' in the Milky Way - Gullberg, Steven R. (2020)
Cultures around the world find meaning in the groupings of stars and features in the Milky Way. The striking appearance of our Galaxy in the night sky serves as a reference to traditional knowledge, encoding science and culture to a memory space, becoming part of their overarching cosmologies. This paper examines traditional views of the Milky Way from cultures around the world, primarily in the Southern Hemisphere. These views comprise dark constellations: familiar shapes made up of the dark dust lanes in the Milky Way, rather than the bright stars. Some of the better-known examples include the celestial emu from Aboriginal traditions of Australia, and the llama in Inca traditions of the Andes. We conduct a comparative analysis of cultural perceptions of ‘dark constellations’ in the Milky Way, examining common cultural themes and meanings at the crossroads of Indigenous Knowledge and Western science with applications to topics ranging from Indigenous Studies to psychology.